1996
DOI: 10.1097/00000539-199602000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Tropisetron for the Prevention of Postoperative Nausea and Vomiting in Women Undergoing Gynecologic Surgery

Abstract: The aim of this study was to evaluate the efficacy of tropisetron, a selective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist, versus placebo in the prevention of postoperative nausea and vomiting in patients undergoing general anesthesia for gynecologic surgery. Ten minutes before induction of general anesthesia, 80 patients received in a double-blind manner a single intravenous (IV) injection of either 5 mg tropisetron or a matching placebo. Anesthesia was induced with thiopental and maintained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 10 publications
1
15
0
3
Order By: Relevance
“…Fischer et al [30] and Alon et al [16] showed that tropisetron is more effective than placebo in preventing PONV after gynecologic operations. Pitkänen et al [31] applied bupivacaine (0.5%) and morphine (0.3 mg) to the subarachnoid space for postoperative analgesia; they could not find any significant difference between tropisetron and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al [30] and Alon et al [16] showed that tropisetron is more effective than placebo in preventing PONV after gynecologic operations. Pitkänen et al [31] applied bupivacaine (0.5%) and morphine (0.3 mg) to the subarachnoid space for postoperative analgesia; they could not find any significant difference between tropisetron and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although 5‐HT 3 receptor antagonists have become clinically important agents in treating postoperative and chemotherapy‐induced nausea and emesis (Alon et al ., 1996; Tang et al ., 1998; Watters et al ., 2001) and in delaying large bowel transit and improving pain and discomfort associated with irritable bowel syndrome (Camilleri et al ., 2000), less attention has been paid to 5‐HT 3 receptor agonists as potential therapeutic agents. Consequently, future studies in this area will require suitable models of intestinal function.…”
Section: Introductionmentioning
confidence: 99%
“…before the start of anesthesia has been found effective for prevention of PONV after breast and gynecologic surgery. [3940]…”
Section: Discussionmentioning
confidence: 99%